Market Social Demand and Preferences for careers in economics and universities that offer them. La Libertad Region, 2016 (SCIÉNDO INGENIUM, 2021)
This research, developed by the National University of Trujillo, La Libertad Region, contains results and conclusions of the social demand of the study programs of Administration, Accounting and Finance and of Economics. Its objective is to know the preferences demanded by 4th and 5th students when choosing a university career, as well as the preference for the university to carry out their higher studies. The study method was descriptive, with a cross-sectional survey-type design, the study population was made up of 4th and 5th grade students of secondary education from the La Libertad Region.) The number of students in the sample for EI selected, was 3438 and for parents, 671. The result obtained places the National University of Trujillo in first place, having as the most preferred career in Economic Sciences the career of Administration followed by Accounting and Economics. It is concluded that in the La Libertad Region, there is a high preference for the National University of Trujillo and its careers in Economic Sciences
Keywords: Social demand; preference; Administration; Accounting and Finance; Economy